Design and Synthesis of several new developed Sulfa Drugs and screening of their Antimicrobial and Antifungal Activities - Raoof, Sura S.; Al-Azzawi, Ahlam Marouf (Iraqi Journal of Science, 2026)
The objective of this study was to design and synthesize novel sulfa drugs by incorporating different cyclic imides into their structures. This goal was achieved in two steps. In the first step, four selected sulfa drugs, including sulfamerazine, sulfamethazine, sulfadiazine, and sulfamethoxazole, were reacted with different cyclic anhydrides, namely (maleic, phthalic, and succinic) anhydrides producing N-Drug amic acids (1-6). In the second step, the dehydration of compounds (1-6) was carried out through a fusion process to produce the target corresponding imides (N-Drug imides) (7-12). The results of the biological activity study indicated that the developed drugs (7-12) show very high antimicrobial.